Fibre sub-type specific conduction reveals metabolic function in mouse sciatic nerve - Rich, Laura; Brown, Angus M. (Wiley, 2018)
The stimulus evoked compound action potential (CAP), recorded using suction electrodes, provides an index of the relative number of conducting axons within a nerve trunk. As such the CAP has been used to elucidate the diverse mechanisms of injury resulting from a variety of metabolic insults to central nervous white matter, whilst also providing a model with which to assess the benefits of clinically relevant neuro-protective strategies. In addition the technique lends itself to the study of metabolic cell-to-cell signalling that occurs between glial cells and neurones, and to exploring the ability of non-glucose substrates to support axon conduction. Although peripheral nerves are sensitive to metabolic insult and are susceptible to diabetic neuropathy, there is a lack of fundamental information regarding peripheral nerve metabolism. A confounding factor in such studies is the extended duration demanded by the experimental protocol, requiring stable recording for periods of many hours. We describe a method that allows us to record simultaneously the stimulus evoked CAPs from A and C fibres from mouse sciatic nerve, and demonstrate its utility as applied to investigations into fibre sub-type substrate use. Our results suggest that C fibres directly take up and metabolise fructose, whereas A fibre conduction is supported by fructose-derived lactate, implying there exist unique metabolic profiles in neighbouring fibre sub-types present within the same nerve trunk.